X-Ray and Spectral Ultraviolet Observations of Periodic Pulsations in a Solar Flare Fan/Looptop - Ryan J. French; Laura A. Hayes; Maria D. Kazachenko; Katharine K. Reeves; Chengcai Shen; Juraj Lörinčík (The Astrophysical Journal)
We present simultaneous X-ray and spectral ultraviolet observations of strikingly coherent oscillations in emission from a coronal looptop and fan structure, during the impulsive phase of a long-duration M-class solar flare. The ≈50 s oscillations are observed near in-phase by Solar Orbiter/STIX, GOES, and IRIS Fe xxi intensity, Doppler, and nonthermal velocity. For over 5 minutes of their approximate 35 minute duration, the oscillations are so periodic (2 σ above the power-law background) that they are better described as “periodic pulsations” than the more widely documented “ quasi periodic pulsations” often observed during solar flares. By combining time-series analysis of the multi-instrument data sets with comparison to magnetohydrodynamic simulations, we attribute the oscillations to the magnetic tuning fork in the flare looptop–fan region, and betatron acceleration within the lower-altitude flare loops. These interpretations are possible due to the introduced Sliding Raster Method (SliRM) for analysis of slit spectrometer (e.g., IRIS) raster data, to increase the temporal cadence of the observations at the expense of spatial information.